Learning Experiences of Frontline Nurses Combating COVID-19 in Public Hospitals - Bajracharya, Rashmila; Pangeni, Shesha Kanta (Journal of Nepal Health Research Council, 2023)
Background: Combating COVID-19 by frontline nurses is highly concerned to manage and maintain the health care delivery system through qualitative services to the infected people. If nurses do not agree to the frontline role to combat COVID-19, it might create massive crisis in health sectors. The purpose of this study was to explore the learning experiences of frontline nurses combating COVID-19 in the public hospitals of Kathmandu valley. Furthermore, this study has explored their stories of combating COVID-19.Methods: Philosophically, this study is guided by interpretive paradigm utilizing the qualitative design with narrative inquiry. Stories were collected using face to face interview with six frontline nurses (seniors and juniors) working at COVID special units in three different public hospitals of Kathmandu valley. I have interpreted shared stories of combating experiences and learning, using self-efficacy theory and resilience theory. Results: This study revealed that the participants faced many challenges related to physical, mental, emotional and psychological and various managerial issues. However, they were able to cope due to their self-willingness, nursing education, altruistic nature and support system. Likewise, they acquired various skills: patient care, managerial and leadership, similarly understanding philosophy of life. Conclusions: Frontline nurses were able to combat COVID-19 successfully. Nowadays, they are happy, satisfied and proud with their roles that they had during the health emergency of COVID-19 pandemic and the commitment they fulfilled.Keywords: Challenges; front line role; leadership skill; learning experiences; support system